Comparing Political Attitudes of Evangelicals with the Attitudes of Mainline Christians and Non-Church Members in The Netherlands. Issue 1 (17th October 2017) - Vermeer, Paul; Scheepers, Peer
Abstract: Evangelicals are generally considered culturally conservative regarding issues like abortion or homosexuality and sometimes also economically conservative regarding issues like tax reduction. But does this image also apply to Dutch evangelicals who live in a secular environment in which they constitute only a tiny fraction of the number of church members? This article explores the political attitudes of Dutch evangelicals with the help of two research questions: (1) Do Dutch evangelicals hold more conservative political attitudes on economic and cultural issues than Catholics, mainline Protestants and non-church members? and (2) Which decisive factors determine the supposed conservatism among Dutch evangelicals as compared to Catholics, mainline Protestants and non-church members? Analyses of survey data show that Dutch evangelicals are indeed culturally conservative, but more liberal in economic matters. In addition, results also show that their cultural conservatism is related to their religious convictions, while their economic attitudes are unrelated to religion.